Click-Derived Triazoles and Triazolylidenes of Manganese for Electrocatalytic Reduction of CO2 - Friães, Sofia (2021)
022162, CEECIND/00509/2017, PTDC/QUI-QIN/28151/2017, RECI/BBB-BEP/0124/2012, SFRH/BD/131955/2017, UIDB/00100/2020, UIDB/04378/2020, UIDB/04612/2020, UIDP/00100/2020, UIDP/04046/2020, UIDP/04378/2020, UIDP/50006/2020, UIPD/04612/2020 Funding Information: This research was funded by FUNDA??O DE CI?NCIA E TECNOLOGIA, FCT, grant numbers: PTDC/QUI-QIN/28151/2017, SFRH/BD/131955/2017, CEECIND/00509/2017. The MOSTMICRO-ITQB was funded by UIDB/04612/2020 and UIPD/04612/2020. The NMR spectrome-ters at CERMAX were funded by 022162. LAQV and UCIBIO were funded by UIDB/50006/2020, UIDP/50006/2020, UIDB/04378/2020, and UIDP/04378/2020. The X-ray infrastructure was funded by RECI/BBB-BEP/0124/2012. The BioISI was funded by UIDB/04046/2020, UIDP/04046/2020, UIDB/00100/2020, and UIDP/00100/2020. We thank C. Almeida for elemental analysis at ITQB laboratories. Funding Information: Funding: This research was funded by FUNDAÇÃO DE CIÊNCIA E TECNOLOGIA, FCT, grant numbers: PTDC/QUI-QIN/28151/2017, SFRH/BD/131955/2017, CEECIND/00509/2017. The MOSTMICRO-ITQB was funded by UIDB/04612/2020 and UIPD/04612/2020. The NMR spectrometers at CERMAX were funded by 022162. LAQV and UCIBIO were funded by UIDB/50006/2020, UIDP/50006/2020, UIDB/04378/2020, and UIDP/04378/2020. The X-ray infrastructure was funded by RECI/BBB-BEP/0124/2012. The BioISI was funded by UIDB/04046/2020, UIDP/04046/2020, UIDB/00100/2020, and UIDP/00100/2020. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.